Vilken information får hundägare i samband med kastrering av sin hanhund? - Ivarsson, Sofia (2014)
BACKGROUND Until 1988, it was forbidden to neuter male dogs in Sweden without a veterinary medical cause, so there is clearly no long tradition of this procedure in healthy dogs. According to the website of The Swedish Kennel Club (SKK), February 11, 2011, there has been an increase of castrated male dogs in Sweden. They see this increase as worrying, especially in cases of the less common breeds, where it is most important to maintain the gene pool. The SKK expresses concern that castration is used as a tool to influence the personality of dogs, instead of training and education of the dog. They write that castration should be preceded by a discussion initiated by the veterinarian, where the pros and cons of castration are weighed against each other. The Swedish Veterinary Association shares the SKK's views and developed a standpoint stating that they do not think veterinarians should recommend castration of healthy dogs without having a discussion with the owner in each case.